Increasing Prevalence of Unique Mutation Patterns in H5N1 Avian Influenza Virus HA and NA Glycoproteins from Human Infections in Egypt. (7th July 2010) - Abdelwhab, El-Sayed M.; Hafez, Hafez M.; Aly, Mona M.; Grund, Christian; Harder, Timm C.
Abstract : Highly pathogenic avian influenza H5N1 virus (HPAIV) continues to be a candidate of a further influenza virus pandemic. Egypt is the country worst affected by human cases of HPAIV H5N1 infection in 2009. Increased infection of preschool children and decreased mortality rates suggested subtle changes in the epidemiology of the infection. Among other factors, the evolution of several conspicuous viral genetic markers in the HA and NA genes of HPAIV H5N1 viruses of human cases from Egypt and their putative influence on biological virus characteristics described here may contribute to this situation.